Non‐alcoholic fatty liver disease in premenopausal women with polycystic ovary syndrome: A systematic review and meta‐analysis. Issue 4 (25th February 2021) - Shengir, Mohamed; Chen, Tianyan; Guadagno, Elena; Ramanakumar, Agnihotram V; Ghali, Peter; Deschenes, Marc; Wong, Philip; Krishnamurthy, Srinivasan; Sebastiani, Giada
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD) and polycystic ovary syndrome (PCOS) are prevalent conditions sharing common pathogenic factors. We performed a systematic literature review and meta‐analysis aiming to investigate the association between NAFLD and PCOS among premenopausal PCOS patients. Methods: Relevant studies were systematically identified from scientific databases until 2019. We calculated pooled odds ratio (OR) using a random‐effect model, and heterogeneity was addressed through I 2 . Subgroup analyses and meta‐regression for various covariates were performed. Results: Of the 1833 studies retrieved, 23 studies with 7148 participants qualified for quantitative synthesis. The pooled result showed that women with PCOS had a 2.5‐fold increase in the risk of NAFLD compared to controls (pooled OR 2.49, 95% confidence interval [CI] 2.20–2.82). In subgroup analyses comparing PCOS to controls, South American/Middle East PCOS patients had a greater risk of NAFLD (OR 3.55, 95% CI 2.27–5.55) compared to their counterpart from Europe (OR 2.22, 95% CI 1.85–2.67) and Asia (OR 2.63, 95% CI 2.20–3.15). Insulin resistance and metabolic syndrome were more frequent in the PCOS group (OR 1.97, 95% CI 1.44–2.71 and OR 3.39, 95% CI 2.42–4.76, respectively). Study quality and body mass index (BMI) were the only covariates that showed a relationship with the outcome in the meta‐regression, with a regression coefficient of −2.219 (95% CI −3.927 to −0.511) and −1.929 (95% CI −3.776 to −0.0826), respectively. Conclusions: This meta‐analysis indicates that premenopausal PCOS patients are associated with 2.5‐fold increase in the risk of NAFLD, and BMI seems to be the main cofactor. Abstract : We performed a systematic literature review and meta‐analysis to investigate the association between NAFLD and PCOS among premenopausal PCOS patients. Of 1833 studies, 23 studies with 7148 participants were included. Women with PCOS had a 2.5‐fold increase in the risk of NAFLD compared to controls (Pooled OR 2.49, 95% CI 2.20‐2.82; I2=55.2%, p=0.001). South American/Middle East populations had a greater risk of NAFLD (OR 3.55, 95% CI 2.27‐5.55).